2015
DOI: 10.1136/jech-2014-205115
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neighbourhood violence and social cohesion on smoking behaviours among a cohort of smokers in Mexico

Abstract: Background Recent increases in violent crime may impact a variety of health outcomes in Mexico. We examined relationships between neighborhood-level violence and smoking behaviors in a cohort of Mexican smokers from 2011–2012, and whether neighborhood-level social cohesion modified these relationships. Methods Data were analyzed from adult smokers and recent ex-smokers who participated in Waves 5–6 of the International Tobacco Control Mexico Survey. Self-reported neighborhood violence and social cohesion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
3
14
1
1
Order By: Relevance
“…Slopen et al 23 found no association between neighbourhood stress, a scale related to safety and trust in the neighbourhood, and smoking behaviour change among a cohort of middle-aged US adults. In contrast, Fleischer et al 18 analysed a cohort of Mexican smokers (mean age 40 years) and found positive associations between neighbourhood social cohesion and both quit attempts and successful quitting. However, the study by Fleischer et al included only 2 years of data and could not evaluate whether smoking behaviour changes were sustained over a longer time period.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Slopen et al 23 found no association between neighbourhood stress, a scale related to safety and trust in the neighbourhood, and smoking behaviour change among a cohort of middle-aged US adults. In contrast, Fleischer et al 18 analysed a cohort of Mexican smokers (mean age 40 years) and found positive associations between neighbourhood social cohesion and both quit attempts and successful quitting. However, the study by Fleischer et al included only 2 years of data and could not evaluate whether smoking behaviour changes were sustained over a longer time period.…”
Section: Discussionmentioning
confidence: 93%
“…Fewer studies have evaluated the effect of neighbourhood problems and crime on smoking intensity, defined as the number of cigarettes smoked per day by current smokers. Prior work found no association with neighbourhood problems;9 17 however, neighbourhood violence/crime was associated with higher smoking intensity 12 18…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Additionally, cross-sectional data has shown that concern for neighborhood problems and disorder is correlated with higher blood pressure, higher BMI, and increased likelihood of tobacco use, all of which negatively associate with ideal cardiovascular health [13,14]. In contrast, more favorable perceptions of social cohesion have been associated with decreased likelihood of tobacco use [15,16]. These associations inform the development of a socio-ecological model specifically tailored to healthcare utilization behavior (Fig 1).…”
Section: Introductionmentioning
confidence: 96%